Estimating treatment coverage in South African ART clinics based on the time trend of the CD4 count distribution at ART initiation and a dynamical epidemiological model - Mazinu, Mikateko Cynthia (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2013.